2017
DOI: 10.31436/imjm.v16i2.1052
|View full text |Cite
|
Sign up to set email alerts
|

Barriers To Utilization Of Oral Health Care Services Among Antenatal Mothers In Kuantan, Pahang

Abstract: Introduction: During pregnancy, increased acidity in the mouth increases the risk of antenatal mother to get dental caries. It is worsen if antenatal mother has morning sickness like vomiting during pregnancy. It can aggravate the problem by exposing the teeth to more gastric acid. In addition, antenatal mothers have hormonal changes that they are more susceptible to periodontal problems. Therefore, it is important for antenatal mother to get dental treatment and use oral health service. This study aim is to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Barriers in oral healthcare primarily centred on cost, public health prioritisation, and access; both organisational and geographical [53][54][55][56]. In Malaysia, studies have indicated dental fear, time constraints, dissatisfaction with the services rendered such as long waiting time and no immediate treatment given by the dentist, and perception of not having any oral health problems as barriers to oral healthcare utilisation [57,58]. By understanding factors which influence utilisation of oral healthcare, improvement in oral healthcare utilisation could be achieved through appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers in oral healthcare primarily centred on cost, public health prioritisation, and access; both organisational and geographical [53][54][55][56]. In Malaysia, studies have indicated dental fear, time constraints, dissatisfaction with the services rendered such as long waiting time and no immediate treatment given by the dentist, and perception of not having any oral health problems as barriers to oral healthcare utilisation [57,58]. By understanding factors which influence utilisation of oral healthcare, improvement in oral healthcare utilisation could be achieved through appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%